LEGALIZATION OF NON-TRADITIONAL MARRIAGES AS A FACTOR UNDERMINING THE MORAL BASIS OF THE FAMILY AND LEADING TO THE REJECTION OF CHRISTIAN VALUES - Viktorovna Alontseva, Dina; Anatolyevna Lavrishcheva, Olga; Vladimirovna Plotnikova, Alexandra; Nikolaevna Kirichenko, Yulia; Vladimirovich Medvedev, Alexey (Gênero & Direito, 2020)
The goal of this research article is to demonstrate that non-traditional marriages not only undermine the moral basis of the institution of the family, and lead to the rejection of traditional values. In order to examine this problem, comparative analysis was chosen as the main research method. Through the exploration of international experience and comparing legal norms, repeating the same mistakes in the area of domestic law and judicial practice can be avoided. This approach also facilitates the assessment of the effectiveness of solving various problems of law enforcement associated with the institutions of marriage and as a consequence, family in modern society. Additionally, the authors employed some other general and private scientific methods. Based on the findings of this work, the following conclusions were drawn: non-traditional marriage is a relationship in which the number of participants, their gender, the method of marriage registration, as well as the method of choosing a partner differ from the generally accepted standard of “the man and the woman” to meet sexual interests and needs of the participants. It is noteworthy that family is the basis of the state, national identity, and cultural development. Without a family in its traditional sense, it is impossible to preserve traditions and to pass them on from one generation to another. Therefore, it is imperative for us and our legislators to seriously consider the legalization of the concept of non-traditional marriages so that they are prohibited and the individuals who are looking to enter into such marriages are persecuted, since these newfangled Western trends are aimed at the destruction of state values and the inexorable degradation of the state itself.